Geographical and sociological imagination in the discourse of urbanism - Kostina, Alina (project baikal, 2025)
The article illustrates the relationship of the sociological (Сh. Mills) and geographical (D. Harvey) imaginations that form the discursive dichotomy of urban planning. The articulation of geographical imagination is associated with the dominance of ‘abstract systems’ of politics and economics (the example of Docklands in London) and is fraught with ‘inaccessibility’ for citizens, the loss of a ‘sense of place’. The sociological imagination is driven by attention to a fragile social topology (the example of Stuyvesant Town in New York) and is aimed at socially oriented projects. The article reveals the potential of Healy’s ‘joint planning’ (Coney Street and Gabriel Shipyards in London), which was proposed to integrate two forms of imagination.